SISTEM PENGENDALIAN INTERN DALAM PROSES PRODUKSI UNTUK MENJAGA KUALITAS PLYWOOD (Studi Kasus pada PT Manunggal Indowood Investindo di Probolinggo) - Puput Maimunah; Farah Adiba (JOURNAL AKSES STIA MALANG, 2021)
This research is inspired from thought of the importance of internal control of production process tomaintain quality. Internal control has an important role in maintaining the fluency operation of company so thatit runs in accordance with the appointed objectives. Internal controls are carried out to reduce misappropriationand to make employees conform with established regulations. Without internal control the company's operationalactivities will not run well and it is possible for misappropriation in its activities. The purpose of this study wasto determine how the production process control system is used in PT Manunggal Indowood Investindo.This type of research is a qualitative descriptive study. The data obtained by the author uses observationtechniques, interview techniques, and documentation techniques. The data analysis technique is descriptiveanalysis using qualitative approach.From the research data obtained by researcher in PT. Manunggal Indowood Investindo, the researcherfound the problem that occurs in the log to rotary section which is there is only one form and only that formcontains information on the date of the wood when it was come, the type of wood, the diagonal wood and thelength of the wood. And it might make a problems, problems that appear when the process immersion woods didnot reach one night. If it is not done overnight, the wood may still be dry and when the rotary part will break, andthe sap that has not been lost can cause dirt on the veneer.From results of theresearch and from the data obtained above the researcher tries to give advice to do1. Making a new form of internal control system, 2. The rotary section makes a request for issuing raw materialsto the log, then the log makes a raw material release form for turned over in the rotary section, 3. We recommendthat the capacity in the immersion pool of raw materials be made more large.Keywords - Production Process, Production Process Internal Control System, Quality Control